2012
DOI: 10.1080/14786419.2011.653971
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antioxidant activity of the essential oil of Tabernaemontana catharinensis A. DC. leaves

Abstract: The essential oils obtained by hydrodistillation from the leaves of Tabernaemontana catharinensis had their composition analysed by GC-MS. A total of 18 substances were identified, consisting of a complex mixture of sesquiterpenes (83.52%), monoterpenes (5.46%) and triterpenes (4.56%). The main components in the oil were β-caryophyllene (56.87%), α-cadinol (12.52%), 8S,13-cedran-diol (5.41%), α-terpineol (3.99%), β-eudesmol (2.54%), caryophyllene oxide (2.51%) and ethyl iso-allocholate (2.03%) along with β-cub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…Relative component concentration was calculated based on GC peak areas without using correction factors. The injection volume of the C. guianensis (andiroba) and M. alternifolia (tea tree) essential oils was 1 µL (Boligon et al , ).…”
Section: Methodsmentioning
confidence: 99%
“…Relative component concentration was calculated based on GC peak areas without using correction factors. The injection volume of the C. guianensis (andiroba) and M. alternifolia (tea tree) essential oils was 1 µL (Boligon et al , ).…”
Section: Methodsmentioning
confidence: 99%
“…Studies conducted by Boligon et al [6] demonstrated that the major constituent in the essential oil of T. catharinensis leaves was β-caryophyllene (56.9%) having anti-inflammatory, antibiotic, antioxidant, anticarcinogenic and local anesthetic activities. Here we report the identification and quantitation of phenolic compounds, for the first time, by HPLC/DAD in the crude extract and fractions of T. catharinensis stem bark.…”
mentioning
confidence: 99%
“…The essential oil of the plant leaves showed antioxidant activity (Boligon et al 2012). Many studies performed with plants resulted in the development of natural antioxidant formulations.…”
mentioning
confidence: 99%